The social determinants of child health and inequalities in child health. Issue 3 (March 2022) - Pickett, Kate E.; Vafai, Yassaman; Mathai, Mathew; Small, Neil
Abstract: Social factors have a profound impact on child health – they are the "causes of the causes", creating social gradients and inequalities in almost all morbidities. The social determinants of health are complex and intertwined, and in the UK child health inequalities are entrenched and intractable. We describe how longitudinal research on children's health and life course trajectories gives us insights into the ways in which the social determinants interact to affect children, and how these insights can shape policy and practice to improve child health. We also touch on three major contemporary issues in child health: adverse childhood experiences, the Covid-19 pandemic and climate change. We explore how paediatricians can engage with the social determinants of child health and be agents for change, and share examples of innovative practice.